2013
DOI: 10.1371/journal.pone.0057607
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Chloroplast Genome Sequence of the Medicinal Plant Salvia miltiorrhiza

Abstract: Salvia miltiorrhiza is an important medicinal plant with great economic and medicinal value. The complete chloroplast (cp) genome sequence of Salvia miltiorrhiza, the first sequenced member of the Lamiaceae family, is reported here. The genome is 151,328 bp in length and exhibits a typical quadripartite structure of the large (LSC, 82,695 bp) and small (SSC, 17,555 bp) single-copy regions, separated by a pair of inverted repeats (IRs, 25,539 bp). It contains 114 unique genes, including 80 protein-coding genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

115
186
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(308 citation statements)
references
References 75 publications
115
186
4
3
Order By: Relevance
“…The sequence demonstrates the typical quadripartite structure of other angiosperms, with a large single copy (LSC) region of 81,364 bp and a small single copy (SSC) region of 17,499 bp, separated by a pair of inverted repeats (IRa and IRb) of 25,436 bp. The length and structure of the sequence is similar to other plastid genome sequences of members in the order Lamiales (Lukas and Novak, 2013;Mariotti et al, 2010;Qian et al, 2013) (Fig. 3, see also Fig.…”
Section: Stenogyne Haliakalae Chloroplast Genome Assembly and Charactsupporting
confidence: 60%
See 2 more Smart Citations
“…The sequence demonstrates the typical quadripartite structure of other angiosperms, with a large single copy (LSC) region of 81,364 bp and a small single copy (SSC) region of 17,499 bp, separated by a pair of inverted repeats (IRa and IRb) of 25,436 bp. The length and structure of the sequence is similar to other plastid genome sequences of members in the order Lamiales (Lukas and Novak, 2013;Mariotti et al, 2010;Qian et al, 2013) (Fig. 3, see also Fig.…”
Section: Stenogyne Haliakalae Chloroplast Genome Assembly and Charactsupporting
confidence: 60%
“…The Hawaiian mint genome did not demonstrate any rearrangements or inversions, which have been found in Jasmin nudiflorum, Schwalbea americana, and a few other species (Welch et al, 2016) (Lee et al, 2007;Wicke et al, 2013). The lengths of the mint chloroplast genomes, including lengths of the inverted repeat and small single copy region, were similar to other species in this family, such as Origanum vulgare and Salvia miltiorrhiza (Lukas and Novak, 2013;Qian et al, 2013), with most of the differences in length being due to short indels within the long single copy region.…”
Section: Mint Chloroplast Genome Structure and Variabilitymentioning
confidence: 57%
See 1 more Smart Citation
“…Compared with other cp genome sequences, Chuanminshen cp genome was smaller than Panax ginseng 156,318 bp (Kim and Lee 2004), Nicotiana tabacum 155,943 bp (Shinozaki et al 1986), and much longer than Salvia miltiorrhiza Bge151328 bp (Qian et al 2013), a model plant of Chinese herbal medicine (Zhang et al 2015). Statistical analysis showed that Chuanminshen is the sixth largest cp genome in size and has the highest GC content among the 15 chloroplast genome sequences (including Chuanminshen) of Apiaceae plant family.…”
Section: Cp Genome General Features Of Chuanminshenmentioning
confidence: 93%
“…Chloroplasts play an important role in photosynthesis and carbon fixation as well as in the biosynthesis of starch, fatty acids, and amino acids [6]. The cp genome ranges from 120 to 180 kb in higher plants and has a quadripartite structure consisting of a large single copy (LSC) and small single copy (SSC) region and two copies of a larger inverted repeat (IR) [7].…”
Section: Introductionmentioning
confidence: 99%